2013
DOI: 10.1007/jhep09(2013)102
|View full text |Cite
|
Sign up to set email alerts
|

R-charged black holes and Holographic optics

Abstract: We analyze momentum dependent vector modes in the context of gauge theories dual to R-charged black holes in D = 4, 5 and 7. For a variety of examples, the master variables are constructed, for which the linearized equations for the perturbations decouple. These allow for the computation of momentum dependent correlation functions. Away from the hydrodynamic limit, numerical analysis using the decoupled equations of motion is used to obtain the analogues of the Depine-Lakhtakia (DL) index. For specified ranges… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…In order to complete our analysis, in figs. (15) and (16) we have shown the variation of n DL with ω for different temperatures. In both these figures red, green, blue and brown curves correspond to T /T c = 0.8, 0.6, 0.4 and 0.2 respectively.…”
Section: −Iω 4πtmentioning
confidence: 93%
See 1 more Smart Citation
“…In order to complete our analysis, in figs. (15) and (16) we have shown the variation of n DL with ω for different temperatures. In both these figures red, green, blue and brown curves correspond to T /T c = 0.8, 0.6, 0.4 and 0.2 respectively.…”
Section: −Iω 4πtmentioning
confidence: 93%
“…These authors showed that the boundary theory corresponding to an Einstein-Maxwell bulk theory at finite chemical potential and temperature in the five dimensional AdS black hole background have n DL < 0 and shows negative refraction in the low frequency regime. It was then subsequently investigated in RN-AdS black hole in four dimensions [14], Rcharged black holes in different dimensions [15] and D7 flavor brane systems [16]. Identical results of negative refraction in low frequency were found in all cases.…”
Section: Introductionmentioning
confidence: 94%
“…which are proportional to the Fourier transforms of the quantities (40). This replacement of variables leads to the following set of perturbation equations:…”
Section: Equations For Tetrad-invariant Scalarsmentioning
confidence: 99%
“…The perturbations of static charged anti-de Sitter black holes have been the focus of great interest in the last years, especially due to their applications to holographic condensed matter systems (see refs. [33][34][35][36][37][38][39][40][41][42] for a sample). In a similar way, rotating uncharged black holes (either in asymptotically flat or AdS spacetimes) have attracted a lot of attention in connection with the Kerr/CFT correspondence [43][44][45][46][47] (see also [48] and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…The former implies that the electromagnetic energy flux and the phase velocity of an electromagnetic wave through the medium propagate in opposite directions [6,[12][13][14][15][16][17][18][19][20][21][22]; the latter means that, even if isotropic, a medium supports multiple electromagnetic waves with the same frequency but different wave-vectors [7][8][9][10][11]. Following these results, various authors investigated these topics in a wide variety of different setups, see for example [26][27][28][29][30][31][32][33][34][35][36]. In particular [37] provides an analysis of the actual signature of the abovementioned phenomena in condensed matter systems and it proposes suitable experiments to measure such effects.…”
Section: Jhep11(2014)153mentioning
confidence: 99%